In vitro antioxidant and protective effects of corn peptides on ethanol-induced damage in HepG2 cells. Issue 1 (2nd January 2016) - She, Xingxing; Wang, Fei; Ma, Jun; Chen, Xi; Ren, Difeng; Lu, Jun
Abstract : To assess the effect of corn peptides (CPs) as an antioxidant on ethanol (EtOH)-induced oxidative stress in HepG2 cells, the cells were preincubated with CPs for 4 h before treated with EtOH. Methyl thiazolyl tetrazolium and flow cytometry assay were performed to detect the viability of CP-treated HepG2 cells and control cells. The activities of lactate dehydrogenase (LDH), alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA) and superoxide dismutase (SOD) were determined by corresponding kits, respectively. The results showed that treatment with 300 mmol/L EtOH for 24 h resulted in a death of around 50% of the HepG2 cells. Pretreatments of appropriate concentrations of CPs (more than 5 mg/mL, particularly at 20 mg/mL) significantly prevented EtOH-induced cytotoxicity and reduced the increase of ALT, AST, LDH and MDA contents, as well as inhibited the reduction of SOD contents in the HepG2 cells, indicating that CPs protected the cells from oxidative damage induced by EtOH metabolism, and thus had a great application potential in hepatoprotective nutraceuticals.